Effect on kacip fatimah (labisia pumila) water extract on mamographic density- a pilot study - Keat, Tan Boon (2006)
Introduction Kacip Fatimah is a traditional herb that contains phytoestrogen and is commonly used by the Malay population in Malaysia to treat various gynecological illnesses. It is also used as an alternative to hormone replacement therapy due to its estrogenic effect. Postmenopausal hormone use is associated with increase in mammographic density and mammographic density is an independent risk factor for breast cancer. Objective Our purpose was to evaluate the effect of Kacip Fatimah (Labisia pumila) water extract on mammographic density in postmenopausal women. Material and Method A prospective, randomized, double-blind placebo-controlled pilot study was conducted. A total of 69 postmenopausal women were equally randomized to receive Kacip Fatimah water extract 140 mg/day, 280 mg/day, 560 mg/day or placebo. Mammograms were performed at baseline and after 6 months of treatment. Mammographic density was evaluated according to percentage scale, BIRAD classification and computer assisted measurement of breast density. Result The categorical assessments showed that there was no significant shift in categorical classification as assessed by BIRAD and percentage categories in either control or treatment groups. There was slight increase in breast density as assessed by computer assisted method although the increases were not statistically significant. The increases in breast density over pretreatment baseline were 0.2 °/o, 0.1 %, 1.5 % and 0.6 % for placebo, 140 mg group, 280 mg group and 560 mg group, respectively. These values were not significantly different from one another. This small increase in breast density might be due to the fact that phytoestrogen is a weak estrogen. Conclusion Kacip Fatimah extract given over a period of 6 months did not significantly affect mammographic density.